2016
DOI: 10.1080/15384101.2016.1191711
|View full text |Cite
|
Sign up to set email alerts
|

Repriming by PrimPol is critical for DNA replication restart downstream of lesions and chain-terminating nucleosides

Abstract: PrimPol is a DNA damage tolerance enzyme possessing both translesion synthesis (TLS) and primase activities. To uncover its potential role in TLS-mediated IgVλ hypermutation and define its interplay with other TLS polymerases, PrimPol−/− and PrimPol−/−/Polη−/−/Polζ −/− gene knockouts were generated in avian cells. Loss of PrimPol had no significant impact on the rate of hypermutation or the mutation spectrum of IgVλ. However, PrimPol−/− cells were sensitive to methylmethane sulfonate, suggesting that it may by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 57 publications
9
112
0
Order By: Relevance
“…However, during primer synthesis the ZnF domain can access ssDNA both upstream and downstream of the AEP domain. Recent studies highlighting the importance of PrimPol's primase activity in vivo 9101112, coupled with the recruitment of the enzyme via RPA70N shown here, argue that PrimPol more likely binds downstream of RPA, with the ZnF bound to ssDNA upstream of the AEP domain, during primer synthesis (Fig. 7b).…”
Section: Discussionmentioning
confidence: 65%
“…However, during primer synthesis the ZnF domain can access ssDNA both upstream and downstream of the AEP domain. Recent studies highlighting the importance of PrimPol's primase activity in vivo 9101112, coupled with the recruitment of the enzyme via RPA70N shown here, argue that PrimPol more likely binds downstream of RPA, with the ZnF bound to ssDNA upstream of the AEP domain, during primer synthesis (Fig. 7b).…”
Section: Discussionmentioning
confidence: 65%
“…Hence, PrimPol may serve to re-prime leading strand templates downstream of UV-induced lesions. Such activity had been demonstrated in vitro with various obstructions that block DNA synthesis and, indeed, primers synthesized by PrimPol can be efficiently extended by pol ε 141, 144, 145 . Clever genetic assays validated this model in vivo .…”
Section: The Gps For Tls: Correlation Between Re-priming the Damagmentioning
confidence: 95%
“…Similar behavior was also observed for PrimPol after UV treatment and PrimPol foci colocalized with UV-induced lesions and PCNA 73, 74 . Survival assays revealed that depletion or knockout of PrimPol sensitizes cells to UV treatment and such behavior was non-epistatic with both pol η and pol ζ 74, 141, 144 . However, re-localization of PrimPol was not observed after DNA strand breaks were generated by ionizing radiation (IR) and PrimPol knockout cells are not sensitive to IR 74 .…”
Section: The Gps For Tls: Correlation Between Re-priming the Damagmentioning
confidence: 99%
See 2 more Smart Citations